2006
DOI: 10.1088/0963-0252/15/4/004
|View full text |Cite
|
Sign up to set email alerts
|

Pinching evidences in a miniature plasma focus with fast pseudospark switch

Abstract: We report the observations of pinching in a miniature plasma focus (PF) (58-160 J) operated in repetitive mode using fast pseudospark switch (PSS). The size of the device, which includes the capacitor bank, PSS and the focus chamber, is of the order of 22 cm ×22 cm × 38 cm. Several diagnostic tools, the gated imager, streak camera, current and voltage probe, are employed simultaneously to confirm the occurrence of pinching in this fast miniature PF device. The device is optimized for operation in neon and hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…The maximum yield of (1.06 ± 0.13) × 10 6 neutrons/shots at 9 mb deuterium gas pressure has already been observed (Silva et al 2003) from a fast plasma focus at 400 J of bank energy. The pinching evidence has been observed in the PF devices operated at very low bank energies of ≈100 J (Soto et al 2001), of 32-102 J (Silva et al 2002), of 50 J (Moreno et al 2003), of 50-70 J (Silva et al 2004) and of 58-160 J (Hassan et al 2006). The generation of extreme ultraviolet (Mohanty et al 2006) as a compact and competent source for lithography, emission of soft x-rays (Mohammadi et al 2007) useful for lithography and production of hard x-rays (Moreno et al 2006, Lorenzo et al 2007 for flash radiography have also been reported.…”
Section: Introductionmentioning
confidence: 82%
“…The maximum yield of (1.06 ± 0.13) × 10 6 neutrons/shots at 9 mb deuterium gas pressure has already been observed (Silva et al 2003) from a fast plasma focus at 400 J of bank energy. The pinching evidence has been observed in the PF devices operated at very low bank energies of ≈100 J (Soto et al 2001), of 32-102 J (Silva et al 2002), of 50 J (Moreno et al 2003), of 50-70 J (Silva et al 2004) and of 58-160 J (Hassan et al 2006). The generation of extreme ultraviolet (Mohanty et al 2006) as a compact and competent source for lithography, emission of soft x-rays (Mohammadi et al 2007) useful for lithography and production of hard x-rays (Moreno et al 2006, Lorenzo et al 2007 for flash radiography have also been reported.…”
Section: Introductionmentioning
confidence: 82%
“…For most all other conditions the rise time of luminous intensity is about 200 ns. That the rapid increase in luminous intensity occurs simultaneously with the sheaths arrival at the anode tip likely indicates the occurrence of a pinch as previous research has demonstrated [43,44]. From event to event luminous intensity appears to vary by 25% due to initial asymmetry or shot to shot variation.…”
Section: μM Dpfmentioning
confidence: 53%
“…Intensely bright regions correspond to high energy and high plasma density. Regions of intense brightness at the anode tip are indicative of a pinch event, and in some cases evidence of a pinch can only be observed optically because electrical signals do not show the characteristic dip in the I t d /d trace accompanied by a simultaneous voltage spike [43,44].…”
Section: Methodsmentioning
confidence: 99%
“…Some efforts have been devoted to either correcting their signals using an appropriate model [19] or using very small probe sizes when compared to the plasma sheath dimensions [20]. These methods are particularly difficult to use on very small plasma focus devices (usually portable and sub-kJ of stored energy) where the physical dimensions of the load and the plasma sheath are in the millimeter range (or even lower) [10,14,[21][22][23][24][25][26]. Additionally, some optical diagnostic methods have been used for determining some sheath properties based on single shot measurements.…”
Section: Introductionmentioning
confidence: 99%